Human hydatidosis in the central Andes of Peru: Evolution of the disease over 3 years - Moro P.L. (1999)
This study was funded in part by the National Institutes of Health (grant no. U01-A135894, awarded to The Johns Hopkins University), the RG-ER Fund, and Consejo Nacional de Ciencia y Tecnologı´a (CONCYTEC; Lima, Peru).